POBEDONOCSEV AND CRITICISM OF MULTI-PARTY REPRESENTATIVE DEMOCRACY - Đurković, Miša (National interest, 2024)
The author deals with the work of Konstantin Pobedonostsev and especially his criticism of multi-party representative democracy. Usually, his refusal to introduce democracy and advocacy of self-states and imperial autocracy are interpreted as personal interests, reactionary, backwardness, etc. But here we show that it was an extremely educated man who was a Westerner by education and who closely followed the development and problems of the Western representative system. The author shows that his work in this field is part of the overall European intellectual debate on changing the system of democracy in the age of mass parties. Following Polunov's work, which showed Western influences on Pobedonostsev's thought, we place his work and argumentation in the context of the Western canon of criticism of multipartyism, which includes Ostrogorski, Belok and Michels, whose works were published years after the Moscow Collection.
Keywords: Pobedonostsev; representative democracy; autocracy; party system; Ostrogorski; Michels